2007
DOI: 10.2983/0730-8000(2007)26[163:ssmotp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Summer Seed Mortality of the Pacific Oyster, Crassostrea Gigas Thunberg Grown in Tomales Bay, California, Usa: The Influence of Oyster Stock, Planting Time, Pathogens, and Environmental Stressors

Abstract: Summer seed mortality (SSM) has occurred yearly in Tomales Bay, California since 1993. SSM has resulted in up to 90% cumulative losses, and has been associated with extreme temperature, phytoplankton blooms, and an oyster herpesvirus. In this study, three stocks of Pacific oysters were planted at three sites in California (Inner Tomales Bay, Outer Tomales Bay, and Bodega Harbor) in October of 2000 (Fall) and April of 2001 (Spring) and monitored for mortality, growth, and health status. In April of 2001, a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…A similar effect of temperature on OsHV-1-related mortality was reported in the field for juvenile oysters in Tomales Bay, USA (Burge et al 2006), and under experimental conditions (Sauvage et al 2009). The influence of temperature on OsHV-1 occurrence and virus expression has also been demonstrated for Crassostrea gigas larvae (Le Deuff et al 1996) and is suspected for juveniles (Renault et al 1995, Friedman et al 2005, Burge et al 2007, Sauvage et al 2009.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…A similar effect of temperature on OsHV-1-related mortality was reported in the field for juvenile oysters in Tomales Bay, USA (Burge et al 2006), and under experimental conditions (Sauvage et al 2009). The influence of temperature on OsHV-1 occurrence and virus expression has also been demonstrated for Crassostrea gigas larvae (Le Deuff et al 1996) and is suspected for juveniles (Renault et al 1995, Friedman et al 2005, Burge et al 2007, Sauvage et al 2009.…”
Section: Introductionsupporting
confidence: 58%
“…This study clearly shows that seawater temperature influences mortality among previously 'exposed' oysters as well as disease transmission to cohabitating healthy animals. The influence of temperature on OsHV-1 occurrence and virus expression has previously been demonstrated for Crassostrea gigas larvae (Le Deuff et al 1996) and suggested for juveniles (Renault et al 1995, Friedman et al 2005, Burge et al 2007, Sauvage et al 2009. However, to our knowledge, the effect of low temperature (i.e.…”
Section: Effect Of Temperature On Disease and Related Mortalitymentioning
confidence: 73%
“…are shed from live oysters. The continual loss of haemocytes via diapedesis is normal (Galtsoff, ), but increases in the presence of pathogens (Burge et al, ; Friedman et al, ; Friedman & Perkins, ; Heasman et al, ). The rate at which haemocytes and therefore Bonamia spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, production of C. gigas has been compromised by widespread and recurrent mortality events [1][2][3][4][5][6]. Mortalities frequently occur during the summer months, with "summer mortality" often used as an umbrella term to encompass mortalities resulting from viral and/or bacterial infection overlaid with (or precipitated by) environmental stressors [1,7,8].…”
Section: Introductionmentioning
confidence: 99%